A concept of Surveying and Mapping Vulnerability and Flood Hazard (with Hydro-Geomorphological Approach) - Suprapto Dibyosaputro (Forum Geografi, 1998)
The general event of natural process phenomena on lowland areas is flood as an effect of the overtooping stream water over natural levees and inundate the area of surrounding the river. Most of the lowland surround the rivers is used by man for settlements, agriculture land, high way, and other activities to support their life intensively. Therefore flood is not only the physical phenomena but also a socio – economic phenomena. One of the way to understand the spatial distribution of flood prone areas an be done by means of survey and mapping of the flood susceptibility and hazard using an hydro- geomorphological approach. The fluvial landform units on the lowlands reflect the effet of the geomorphological and hydrological processes in the past. Therefore those phenomena can be applied to explain the recent flood characteristics such as inundation  area, depth and flood duration, as well as flood frequencies and sources of floods. This explanation can be used as the starting point of the existing information which an be used as a basic survey and mapping of the flood suspectibility and hazard. The exiting of the interaction between man and natural event (flood) information, can also be applied as a fundament to define the hazard levels of every landform units own flood susceptibility levels.